Failure prediction of multi-cracked ductile polymeric specimens under mixed mode I/II loading. (October 2020) - Pourseifi, M.; Rahimi, A.S.
Highlights: Ductile polymeric specimens containing multiple cracks are fabricated and tested under mixed mode I/II loading. The Equivalent Material Concept is combined with the dislocation method and generalized maximum tangential stress criterion. FE models are used to obtain the fracture toughness of specimens and to perform elastic–plastic simulation. Good consistency is found between the experimental and theoretical results. Abstract: Elastic-plastic failure of multi-cracked specimens made from epoxy material is studied theoretically and experimentally for the first time under mixed mode I/II loading conditions. Different cracks arrangements are considered for preparing the specimens. For providing different mixed mode I/II loading conditions in the fracture tests on epoxy specimens, different crack inclination angles are considered in the samples. Load-carrying capacities (LCCs) of the multi-cracked specimens are obtained experimentally by performing fracture tests. In order to avoid the complex and time-consuming elastic–plastic failure predictions, the Equivalent Material Concept (EMC) is used in conjunction of the dislocation method and generalized maximum tangential stress criterion to obtain experimental and theoretical fracture parameters. It is demonstrated that the proposed combined approach can provide reliable predictions of fracture toughness and fracture estimation under mixed mode I/II loading.